2013
DOI: 10.1177/1477153513503170
|View full text |Cite
|
Sign up to set email alerts
|

Lamp spectrum and spatial brightness at photopic levels: A basis for developing a metric

Abstract: Light sources are available in a variety of spectral power distributions (SPDs) and this affects spatial brightness in a manner not predicted by quantities such as illuminance. Tuning light source SPD to better match the sensitivity of visual perception may allow the same spatial brightness but at lower illuminance with potential reductions in energy consumption. Consideration of experimental design was used to review 70 studies of spatial brightness. Of these, the 19 studies considered to provide credible evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 83 publications
(192 reference statements)
1
24
0
Order By: Relevance
“…13,14 Many past studies have investigated the influence of spectral power distribution on spatial brightness, [15][16][17][18][19][20][21][22][23][24][25] Fotios et al provide a useful review. 26 Other studies have investigated the relationship between spatial brightness and light on a vertical plane 27 and also luminance within a defined field of view. 28, 29 Rea et al found illuminance on a vertical plane to correlate better with assessments of brightness than that of light on a horizontal plane.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Many past studies have investigated the influence of spectral power distribution on spatial brightness, [15][16][17][18][19][20][21][22][23][24][25] Fotios et al provide a useful review. 26 Other studies have investigated the relationship between spatial brightness and light on a vertical plane 27 and also luminance within a defined field of view. 28, 29 Rea et al found illuminance on a vertical plane to correlate better with assessments of brightness than that of light on a horizontal plane.…”
Section: Introductionmentioning
confidence: 99%
“…Here we refer to the 20 out of 29 studies collated within a review (Fotios 2017) of Kruithof-type research that did not meet recommended best practice (CIE 2014a); for example, that in a repeated measures design the different scenes were observed in a random order, that data were statistically analyzed, and that sufficient details of the work were reported to repeat the experiment. Particular criticism may be directed to those Kruithof studies conducted after the 1990 publications of Boyce and Cuttle (1990) and Davis and Ginthner (1990), both of which presented results that disagree with Kruithof. Similarly, a review of spatial brightness studies suggested that only 19 out of 70 studies provided credible data (Fotios et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Reassurance is associated with spatial brightness (Blöbaum and Hunecke 2005) and spatial brightness is modified by changes in the illuminance and spectrum of lighting (Fotios and Cheal 2011;Fotios et al, 2015aFotios et al, , 2015b. Several studies have used category rating to evaluate reassurance at different illuminances, tending to conclude that higher illuminances bring greater reassurance.…”
Section: Introductionmentioning
confidence: 99%